Durability of foamed concrete with processed spent bleaching earth as partial replacement of cement under chloride environment - Ting, Qiang Chao (2017)
Formerly, the uses of the pozzolan materials such as fly ash, silica fume and ground granulated blast-furnace slag as replacement in the production of the concrete have proven to increase the durability of the concrete due to its pozzolanic effect. Besides the utilization of pozzolan materials from the industrial waste as a construction materials lead to reduce the cost of construction materials and reduce the environmental impact from the waste. Processed Spent Bleaching Earth (PSBE) is the SBE that has been treated and can be used as a partial replacement for cement in the foamed concrete due to its pozzolanic effect. The objective of the study is to investigate the effect of the Processed Spent Bleaching Earth in increasing the durability of the foamed concrete against chloride attack. Four mixtures of foamed concrete were design for density of 1600 kg/m3. Foamed concrete (FC) mix with 100% OPC was designed as basic control mix. Processed Spent Bleaching Earth Foamed Concrete mixes (PFC) were designed by partial replacement of cement with 10%, 20% and 30% of PSBE by weight of cement namely as PFC1, PFC2 and PFC 3 respectively. In this study, cube specimen 100mm x 100mm x 100mm and cylinder specimen 200mm diameter x 100mm were prepared and tested based on ASTM C513-11 and ASTM C1202 for compressive strength and durability of foamed concrete towards chloride environment. All specimens were subjected to water curing for 28 days before immersed in the 5% Sodium Chloride solution with pH 6.5 for 7, 28, 60 and 90 days. The behaviour of foamed concrete specimen was observed weekly where the physical and mass loss of the specimens was measured at every week until the end of testing procedure. The cylinder specimens were prepared for rapid chloride permeability test (RCPT) and thermal conductivity test. The findings showed that specimens containing PSBE experienced lower percentage of mass change as compared to control specimen. Results exhibit that 30% of PSBE performed better performance in strength and durability of foamed concrete exposed to chloride environment. In addition, the physical deterioration of 30% of PSBE was lower than control mixture. Hence, the integration of PSBE as partial cement replacement enhances the resistance of foamed concrete towards chloride environment.